2011
DOI: 10.1016/j.bpj.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Pathway for Water Permeation through Sodium-Glucose Cotransporters

Abstract: Although water permeation across cell membranes occurs through several types of membrane proteins, the only permeation mechanism resolved at atomic scale is that through aquaporins. Crystallization of the Vibrio parahaemolyticus sodium-galactose transporter (vSGLT) allows investigation of putative water permeation pathways through both vSGLT and the homologous human Na-glucose cotransporter (hSGLT1) using computational methods. Grand canonical Monte Carlo and molecular dynamics simulations were used to stably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…This, or closely related conformational states, are poised to release both Na + and sugar through that passage, and consistent with a strict alternating-access mechanism, the X-ray structure exhibits a thick outer gate that occludes the substrate site from the extracellular space. Simulations of vSGLT have revealed that this outer gate is permeable to water, which crosses the transporter through the sugar binding site, and that water flow is modulated by the transient formation of an opening on the extracellular face of the transporter (18)(19)(20)(21). In 2 of our 21 simulations, the galactose escapes to the extracellular bulk through the same opening.…”
Section: Resultsmentioning
confidence: 82%
“…This, or closely related conformational states, are poised to release both Na + and sugar through that passage, and consistent with a strict alternating-access mechanism, the X-ray structure exhibits a thick outer gate that occludes the substrate site from the extracellular space. Simulations of vSGLT have revealed that this outer gate is permeable to water, which crosses the transporter through the sugar binding site, and that water flow is modulated by the transient formation of an opening on the extracellular face of the transporter (18)(19)(20)(21). In 2 of our 21 simulations, the galactose escapes to the extracellular bulk through the same opening.…”
Section: Resultsmentioning
confidence: 82%
“…Thus, the introduced mutation removes a barrier that obstructs the Na ϩ leak (either sterical or electrostatic) but does not eliminate a significant barrier for water movement. Previous oocyte experiments report contradictory results: removal of external Na ϩ either eliminated the water conducting ability of SGLT1 (27) or augmented it (28).…”
mentioning
confidence: 91%
“…The agreement is surprising, because the SGLT1 conformations in cells and vesicles are not necessarily the same: The membrane potential is maintained at Ϫ30 mV in living MDCK cells, whereas it is either positive inside shrunken vesicles (because of the up-concentration of Na ϩ ) or clamped to 0 by the protonophore CCCP and the K ϩ -ionophore valinomycin. Previous oocyte experiments also revealed a weak potential dependence: the water permeability of SGLT1 overexpressing oocytes changed by only ϳ20% when the membrane potential was decreased from Ϫ20 to Ϫ100 mV (28).…”
mentioning
confidence: 99%
“…The hypotheses regarding the mechanism of the water absorption-promoting effect of SGLT1 are roughly divided into two types: (1) passive water transport driven by the local osmotic gradient formed by the transport of the substrates (Duquette et al, 2001;Sasseville et al, 2011), and (2) active water transport coupled with the transport of the substrates at the molecular level (Loo et al, 1996(Loo et al, , 2002. Peptide transport by PepT1 may also promote water absorption, as described by these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Na + can therefore be absorbed efficiently when it is ingested with glucose. It was reported that water absorption is promoted by SGLT1 along with the absorption of Na + and glucose (Duquette et al, 2001;Loo et al, 1996Loo et al, , 2002Sasseville et al, 2011).…”
Section: Introductionmentioning
confidence: 99%